Temporal response pattern of biochemical analytes in experimental diabetes - Mori, D. M.; Baviera, A. M.; Ramalho, LTD; Vendramini, R. C.; Brunetti, Iguatemy Lourenço [UNESP]; Pepato, M. T. (Portland Press, 2003)
The activities of the enzymes aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), lactate dehydrogenase (LD), creatine kinase (CK), amylase (AMS) and angiotensin converting enzyme (ACE) have been used to assess the toxic effects of xenobiotics that have hypoglycaemic action in hepatic, pancreatic, renal and muscle tissue. Using a validated experimental model of diabetes mellitus in rats, we ascertained whether this syndrome itself affected the serum activities of these enzymes over a 53-day period. Levels of hepatic enzymes AST, ALT and ALP were higher in the streptozotocin (STZ)diabetic rats (group D), but were controlled by insulin therapy (group DI). AMS was reduced in group D and unchanged in group DI rats. Proteinuria was detected 1 day after STZ administation and partially controlled by insulin (group DI); its early presence in group D rats, and the lack of any change in serum ACE in this group, indicates that proteinuria is the better marker for microangiopathy. Microscopic examination of liver, kidney, heart and skeletal muscles (soleus and extensor digitorum longus) revealed various alterations in group D rat tissues, which were less pronounced in group DI. The liver, pancreas and kidney tissue-damage was consistent with the altered serum levels of AST, ALT, ALP and AMS and proteinuria. We conclude that: (i) rigorous control is required when these serum-enzyme levels are used as indicators of tissue toxicity in experimental diabetes, and (ii) LD, CK and bilirubin serum levels, which are unaffected by diabetes, can be used when testing effects of xenobiotics on tissues.
Keywords: alanine aminotransferase; alkaline phosphatase; aspartate aminotransferase; streptozotocin (STZ)-diabetic rat; seric enzyme; streptozotocin